ANALISIS PEMBERDAYAAN SUBAK TERHADAP OPERASIONAL DAN PEMELIHARAAN JARINGAN IRIGASI SUBAK KEPAON KECAMATAN DENPASAR SELATAN - Ngurah Purbawijaya, Ida Bagus (Jurnal Ilmiah Teknik Sipil; Vol. 16, No. 1 Januari 2012)
Subak Kepaon is located in South Denpasar District consisting Munduk Tungging, Munduk Wang Biga, Munduk Dajan Sema, Munduk Juwet, Munduk Timbul, and Munduk Teruna. Subak Kepaon is situated on the land of 223.76 ha. Tukad Badung (Badung river) flows through the middle of Denpasar and Badung regency towards Subak Kepaon. The main river has a length of 17 km and the main river catchment area is 22.55 km². This river has three functions: irrigation, drainage and raw water taps source (Department of Agriculture and Marine, Denpasar, 2006). This study analyses significant effect of empowerment towards maintenance of Subak Kepaon, South Denpasar District. Based on regression model results, the empowerment variable has a positive slope with a significance value of t test below 5%. This indicates that if the empowerment variable increases so will the maintenance variable. The Fcountvalue of 420.477 is much higher than F table of 2.7746 so that Ho is rejected and Hi is accepted. The Hi describes that empowerment simultaneously influences on maintenance variables. The tcount value of 20.506 is higher than ttable of 1.666 so that Ho is rejected and Hi is accepted. The Hi describes that the positive effect of empowerment exists towards maintenance variables.
Keywords: empowerment, operational and maintenance